2013
DOI: 10.1002/jcph.212
|View full text |Cite
|
Sign up to set email alerts
|

Characteristics and publication patterns of obstetric studies registered in ClinicalTrials.gov

Abstract: Physiologic changes during pregnancy alter the pharmacokinetics, safety, and efficacy of many drugs. For clinicians, there is often uncertainty regarding the safety of these drugs due to a scarcity of published data. This study aimed to comprehensively evaluate the characteristics and publication patterns of obstetric studies registered in ClinicalTrials.gov from 2007-2012. Primary outcome measures, funding sources, inclusion criteria, and the reporting of study results were evaluated. A manual review of Medli… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
18
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(19 citation statements)
references
References 32 publications
0
18
1
Order By: Relevance
“…Another positive finding is that a comparatively large proportion of finished GCTs have already been published in peer-reviewed biomedical journals. Our observed publication rate (71%) of registered GCTs is higher than the rates observed in other clinical trials [ 11 , 23 26 ]. Reasons for failure to publish include lack of positive results, time restriction, limited resources, change of interests, or simply failure to have the paper accepted by a journal [ 26 ].…”
Section: Discussioncontrasting
confidence: 78%
“…Another positive finding is that a comparatively large proportion of finished GCTs have already been published in peer-reviewed biomedical journals. Our observed publication rate (71%) of registered GCTs is higher than the rates observed in other clinical trials [ 11 , 23 26 ]. Reasons for failure to publish include lack of positive results, time restriction, limited resources, change of interests, or simply failure to have the paper accepted by a journal [ 26 ].…”
Section: Discussioncontrasting
confidence: 78%
“…The study by Stockmann et al . examined the characteristics of obstetric studies registered within http://clinicaltrials.gov from 2007 to 2012, demonstrating that these studies represented less than 10% of the total number registered. The authors also found that more than 80% of obstetric studies registered from 2007 to 2012 incorporated elements of high‐quality trial design (e.g.…”
Section: Steps That Can Be Taken To Expand Obstetric Clinical Pharmacmentioning
confidence: 99%
“…Moreover, some journals require published studies to have been preregistered in an appropriate site (Laine, Horton, DeAngelis, et al, 2007;Palma, & Zietman, 2015). ClinicalTrials.gov contains information about a large number of public and commercial trials (Califf, Zarin, Kramer, Sherman, Aberle, & Tasneem, 2012;Hirsch, Califf, Cheng, et al, 2013;Ross, Mulvey, Hines, Nissen, & Krumholz, 2009;Stockmann, Sherwin, Koren, et al, 2014;Zarin, Tse, & Ide, 2005;Zarin, Tse, Williams, Califf, & Ide, 2011) and so it is now possible to count citations from clinical trials records. These citations can therefore be evaluated as a new source of evidence about the health benefits promise of medical research.…”
Section: Introductionmentioning
confidence: 99%